Experimental investigation of jatropha curcas bio-oil and biodiesel in electric discharge machining of Ti-6Al-4V. (2021) - Basha, S.M.; Dave, H.K.; Patel, H.V.
Abstract: Electric Discharge Machining (EDM) is thermal energy based advanced machining process used to machine any electrically conductive material irrespective of its physical properties like strength and hardness. Material removal generally occurs due to continuous recurring of the electrons from the cathode to anode. Dielectric fluid is an unavoidable component in the EDM process where it has a significant effect on machining characteristics like Material Removal Rate (MRR), Tool Wear Rate (TWR), and End Wear Ratio (EWR). Bio-oil/biodiesel based dielectric fluids are suitable substituents for conventional hydrocarbon dielectric fluids, which are carcinogenic. In this present work, Jatropha bio-oil and biodiesel are employed to check their performance to machine Ti-6Al-4V with the EDM process. Taguchi experimental design is applied to find out the combination of optimum process parameters that results to get maximum MRR and EWR and minimum TWR. Analysis of Variance (ANOVA) is carried out to know the significance level of each process parameter upon response characteristic. Based on ANOVA, irrespective of dielectric fluid used for machining, it is found that current is the only significant parameter for MRR, TWR, and EWR.